Genetic Signature and Serocompatibility Evidence for Drug Resistant Campylobacter jejuni - Rozan O. Al-Khresieh; Hala I. Al-Daghistani; Saeid M. Abu-Romman; Lubna F. Abu-Niaaj (MDPI AG, 2022)
Campylobacteriosis, a foodborne illness, is one of the world's leading causes of gastrointestinal illness. This study investigates the link between human campylobacteriosis and the consumption of potentially contaminated food with Campylobacter jejuni. Three hundred sixty samples were collected from humans, chicken cloaca, raw chicken meat, unpasteurized milk, and vegetables. The chickens were obtained from licensed and non-licensed slaughterhouses, and only the necks and wings were studied. Samples were enriched under microaerobic conditions then cultured on the modified charcoal cefoperazone deoxycholate agar. Bacteria was identified by staining, biochemical testing, and molecular identification by the polymerase chain reaction for the virulence genes; hipO, asp, dnaJ, cadF, cdtA, cdtB, and cdtC. The genomic homogeneity of C. jejuni between human and chicken isolates was assessed by the serological Penner test and the pulse field gel electrophoresis (PFGE). Campylobacter was not detected in the vegetables and pasteurized milk, though, only twenty isolates from chickens and clinical samples were presumed to be Campylobacter based on their morphology. The biochemical tests confirmed that five isolates were C. coli, and fifteen isolates were C. jejuni including two isolates from humans, and the remaining were from chickens. The colonization of C. jejuni in chickens was significantly lower in necks (6.66%) obtained from licensed slaughterhouses compared to those obtained from non-licensed slaughterhouses (33.3%). The antimicrobial susceptibility test showed that all identified C. jejuni isolates were resistant to antibiotics, and the majority of isolates (53.5%) showed resistance against six antibiotics, though, all isolates were resistant to ciprofloxacin, tetracycline, and aztreonam. The Penner test showed P:21 as the dominant serotype in isolates from humans, necks, and cloaca. The serohomology of C. jejuni from human isolates and chicken necks, wings, and cloaca was 71%, 36%, 78%, respectively. The PFGE analysis of the pattern for DNA fragmentation by the restriction enzyme Smal showed a complete genotypic homology of C. jejuni human isolates and chicken necks compared to partial homology with cloacal isolates. The study brings attention to the need for effective interventions to ensure best practices for safe poultry production for commercial food chain supply to limit infection with foodborne pathogens, including Campylobacter.